Implementasi Perancangan Sistem Pendukung Keputusan Seleksi Penerima Beasiswa Menggunakan Metode Weight Product (WP) pada SMK Kesuma Bangsa 1 Berbasis Web - Andika Gustiawan; Sartika Lina Mulani Sitio (Journal of Artificial Intelligence and Innovative Applications (JOAIIA), 2022)
Decision support system as a computer-based system that helps in the decision-making process. Decision support system as a computer-based information system that is adaptive, interactive, flexsible,which was specifically developed to support the solution of unstructurer management problems to improve the quality of decision making. This decision support system helps in the decision-making process in theselection of scholarship recipients at SMK Kesuma Bangsa 1, in this decision support system criteria are needed to determine who will be selected to receive the scholarship. The development of this decisionsupport system the author uses the Weight Product method as a decision-making method. The weight product method was chosen because it is a weighted summation to find the weight sum of the performanceratings for each alternative in all attributes. Then the result of the scholarship selection decision are the 10 th alternative out of 10 alternatives with a value of 0.1036z.